If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8 = 3 + -2(c + -4) + 3 Reorder the terms: -8 = 3 + -2(-4 + c) + 3 -8 = 3 + (-4 * -2 + c * -2) + 3 -8 = 3 + (8 + -2c) + 3 Reorder the terms: -8 = 3 + 8 + 3 + -2c Combine like terms: 3 + 8 = 11 -8 = 11 + 3 + -2c Combine like terms: 11 + 3 = 14 -8 = 14 + -2c Solving -8 = 14 + -2c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '2c' to each side of the equation. -8 + 2c = 14 + -2c + 2c Combine like terms: -2c + 2c = 0 -8 + 2c = 14 + 0 -8 + 2c = 14 Add '8' to each side of the equation. -8 + 8 + 2c = 14 + 8 Combine like terms: -8 + 8 = 0 0 + 2c = 14 + 8 2c = 14 + 8 Combine like terms: 14 + 8 = 22 2c = 22 Divide each side by '2'. c = 11 Simplifying c = 11
| 8+20x=x-4 | | P=50h+200 | | 100x=1000findx | | 2x+21+90=80 | | 4x*5=125 | | 45x+75z=339 | | 3x+2(4x+7)=113 | | 17x^2-17=0 | | 21+6x=23+7x | | -3w+2=14 | | 25000x-5y=0 | | X+1.23=65.6 | | 15y-1=103 | | 9x-38=4x+23 | | 11-(x-2)=3 | | 4x+6=9x+1 | | 3x+3(5x-15)=63 | | 8+c=0 | | 8=c-12 | | x^2-14x+40=40 | | -0.23076923p=-2 | | -4(t-4)+9t=7t-6 | | (x-10)(x-4)=40 | | -3(1.2)(1.2)= | | 7y+5=9y | | 36.86=7g+3.54 | | -16-2n=n-4 | | 3(x+2)-7x=9(x-18)+9x-2 | | (23x+5)=22 | | -3+2x=1+x | | 30+10x=9x | | 6x+2(3x-7)=82 |